Comment on "Amplification of endpoint structure for new particle mass measurement at the LHC" - Barr, A; Gwenlan, C; Lester, C; Young, C (American Physical Society, 2011)
We present a comment on the kinematic variable mCT2 recently proposed in [1]. The variable is designed to be applied to models such as R-parity conserving Supersymmetry (SUSY) when there is pair production of new heavy particles each of which decays to a single massless visible and a massive invisible component. It was proposed in [1] that a measurement of the peak of the mCT2 distribution could be used to precisely constrain the masses of the SUSY particles. We show that when Standard Model backgrounds are included in simulations, the sensitivity of the mCT2 variable to the SUSY particle masses is more seriously impacted for mCT2 than for other previously proposed variables.